Breast milk contains probiotics with anti‐infantile diarrhoea effects that may protect infants as they change to solid foods. (26th March 2021) - Niu, Haiyue; Zhou, Xiaohong; Zhang, Xuguang; Liu, Tongjie; Wu, Yifan; Lyu, Linzheng; Liang, Cong; Chen, Shiwei; Gong, Pimin; Zhang, Jiliang; Han, Xue; Jiang, Shilong; et al.
Summary: Infants often experience complementary food‐induced diarrhoea (CFID), which occurs when infants switch from breast milk to solid foods. The relative abundances of Prevotella and Rothia were higher in stools of infants with CFID, while the relative abundances of Enterococcus and Escherichia were higher in healthy infants. The abundance of Lactobacillus spp . normally found in breast milk fed to infants with CFID was significantly reduced, and Enterococcus spp. were less abundant when diarrhoea occurred. Furthermore, Lactobacillus and Enterococcus were present as shared bacteria in both mother and infant, and they were considered potential anti‐CFID probiotics as their relative abundances in breast milk were negatively correlated to infant CFID. Kyoto encyclopedia of genes and genomes (KEGG) functional analysis showed that the function of amino acid metabolism differed between infants with CFID and healthy infants. Therefore, CFID might be related to the decomposition of proteins in food supplements. The screening revealed seven hydrolytic casein and five hydrolytic casein and rice protein isolates from 320 suspected Lactobacillus and Enterococcus isolates. The animal experiments demonstrated that a mixture of five isolates effectively hydrolysed the casein and rice protein and prevented diarrhoea in young rats. Thus, the occurrence of CFID was found to be closely related to the intestinal and breast milk microbiota, and bacteria that could assist in the digestion of cereal proteins were involved in CFID.